Examining behavioral drivers of domestic gastronomy consumers toward street food in Jakarta - Redha Widarsyah; Tania Adiarini; Nurhayati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Street food in Indonesia is a major attraction for both domestic and international visitors in Indonesia. Street food has also become a regional highlight in many ASEAN countries, as demonstrated by the growing interest among researchers in studying the street food scene of the region. For this reason, understanding the factors that motivate consumers’ purchasing decisions is crucial to further developing and strengthening Indonesia’s street food gastronomy ecosystem. This study aims to explore the factors that influence gastronomy consumers’ intentions to revisit street food in Indonesia, focusing on Jakarta’s street food scene. The research sample consists of 218 Indonesian gastronomic customers, via an online marketing research firm from across geographical provinces. Multiple linear regression analysis reveals that food quality ( b=0.406 ,a<.05 ) and service quality( b=0.431 , a<.05 ) are significant drivers for visitors’ repeat purchases of street food in Jakarta. In contrast, factors such as hygiene (as a risk) ( b= 0.063, a>.05 ) and price (as a motivator) ( b= 0.023, a>.05) were not found to significantly influence consumers’ decisions to repurchase street food in Jakarta. The study provides practical implications for tourism stakeholders in Indonesia and offers recommendations for future research.